The encrustation and blockage of long-term indwelling bladder catheters: a way forward in prevention and control - Stickler, D J; Feneley, R C L (Spinal cord, 2010)
Objectives: To review the literature showing that understanding how Foley catheters become encrusted and blocked by crystalline bacterial biofilms has led to strategies for the control of this complication in the care of patients undergoing long-term indwelling bladder catheterization. Methods: A comprehensive PubMed search of the literature published between 1980 and December 2009 was made for relevant articles using the Medical Subject Heading terms ‘biofilms’, ‘urinary catheterization’, ‘catheter-associated urinary tract infection’ and ‘urolithiasis’. Papers on catheter-associated urinary tract infections and bacterial biofilms collected during 40 years of working in the field were also reviewed. Results: There is strong experimental and epidemiological evidence that infection by Proteus mirabilis is the main cause of the crystalline biofilms that encrust and block Foley catheters. The ability of P. mirabilis to generate alkaline urine and to colonize all available types of indwelling catheters allows it to take up stable residence in the catheterized tract in bladder stones and cause recurrent catheter blockage. Conclusion: The elimination of P. mirabilis by antibiotic therapy as soon as it appears in the catheterized urinary tract could improve the quality of life for many patients and reduce the current expenditure of resources when managing the complications of catheter encrustation and blockage. For patients who are already chronic blockers and stone formers, antibiotic treatment is unlikely to be effective owing to the resistance of cells in the crystalline biofilms. Strategies such as increasing fluid intake with citrated drinks could control the problem until bladder stone removal can be organized.